1998
DOI: 10.1046/j.1460-9568.1998.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesolimbic dopaminergic mechanisms underlying individual differences in sugar consumption and amphetamine hyperlocomotion in Wistar rats

Abstract: Individual differences within strains of rats have been demonstrated for dopamine-mediated behaviours and responses to dopaminergic drugs. Differences in mesolimbic dopamine function may underlie individual differences in some of these behaviours, including sugar consumption and amphetamine hyperlocomotion. The present study addressed two potential mechanisms for these differences in dopamine-mediated behaviours. The possibility of functional differences in dopamine receptor subtypes was tested in LOW and HIGH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…This finding parallels reports that amphetamine caused a greater locomotor response and a greater increase in extracellular dopamine in the nucleus accumbens in high sugar feeders than in low sugar feeders (Sills and Vaccarino 1994;Sills and Crawley 1996). When microdialysis samples were collected during access to sucrose, high sugar feeders consumed more sucrose than low feeders and showed an increase above baseline in extracellular dopamine in the nucleus accumbens; dopamine levels in the accumbens of low sucrose feeders did not increase above baseline (Sills et al 1998).…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…This finding parallels reports that amphetamine caused a greater locomotor response and a greater increase in extracellular dopamine in the nucleus accumbens in high sugar feeders than in low sugar feeders (Sills and Vaccarino 1994;Sills and Crawley 1996). When microdialysis samples were collected during access to sucrose, high sugar feeders consumed more sucrose than low feeders and showed an increase above baseline in extracellular dopamine in the nucleus accumbens; dopamine levels in the accumbens of low sucrose feeders did not increase above baseline (Sills et al 1998).…”
Section: Introductionsupporting
confidence: 87%
“…injection of 0.9% saline) (Sills and Vaccarino 1994;Sills and Crawley 1996;Sills et al 1998). It has been suggested that the differences observed between high and low sucrose feeders in response to amphetamine may actually be due to differences in stress sensitivity (Sills and Vaccarino 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon parallels the enhancement, by food restriction, of drug self-administration (Carroll and Meisch 1984) and conditioned place preference (Bell et al 1997), and appears to reflect an increase in sensitivity of the neural substrate for drug reward (Cabeza de Vaca and Carr 1998). The augmentation of drug reward by food restriction is just one of numerous observations that support an association between drug-seeking and ingestive behavior (Sills et al 1998;Gosnell et al 1995;Comer et al 1996;Sills and Vaccarino 1994;Gosnell 2000). Although the physiological mechanisms underlying the augmentation of drug reward by food restriction have not been established, the augmented rewarding effect of amphetamine in food-restricted subjects is associated with increased cfos expression in limbic forebrain dopamine terminal areas (Carr and Kutchukhidze 2000).…”
Section: Introductionmentioning
confidence: 59%
“…Dopamine (DA) has been implicated in various types of learning, likely through actions on synaptic plasticity (Calabresi et al, 2007) and/or motivation (Wise, 2006). Acting through its D1-type (D1 and D5) and D2-type (D2, D3, and D4) receptors, DA mediates learning about novel flavors and spontaneous flavor preferences Cooper, 1988, 1989;Sills et al, 1998), such that the two DA receptor (DAR) types are similarly involved in the former, but affect the latter differently (Rusk and Cooper, 1988, 1994Yu et al, 2000a, b;Baker et al, 2003;Cooper and Al-Naser, 2006).…”
Section: Introductionmentioning
confidence: 99%